1973
DOI: 10.1017/s0016672300012854
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gene dosage and hormones on the expression of Dr in the platyfish,Xiphophorus maculatus(Poeciliidae)

Abstract: SUMMARYPlatyfish, Xiphophorus maculatus, are polymorphic for the patterns red-dorsal (Dr) and spotted-dorsal (Sd) fins, both controlled by closely linked loci on the X chromosome of Jamapa strain, Jp 163A. The intensity of red pigment looks the same in males and females, but spectrophotometric analysis of dorsal fin extracts showed that heterozygous intact males have significantly more red pigment (drosopterin) than homozygous or heterozygous females or castrated males. The mechanism of Dr expression in Jamapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Studies of pigment cells in platyfish have established that a number of types of coloration are expressed, including black melanins, red, orange, and yellow carotenoids, and yellow, orange, red, and reddish brown pterins. 20,24,[26][27][28]34 These studies have also characterized the genetic basis of at least 42 different color patterns (Table 1). (The adult expression of these patterns and the pertinent references are given in the Appendix.)…”
Section: The Genetic Basis Of Coloration In X Maculatusmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of pigment cells in platyfish have established that a number of types of coloration are expressed, including black melanins, red, orange, and yellow carotenoids, and yellow, orange, red, and reddish brown pterins. 20,24,[26][27][28]34 These studies have also characterized the genetic basis of at least 42 different color patterns (Table 1). (The adult expression of these patterns and the pertinent references are given in the Appendix.)…”
Section: The Genetic Basis Of Coloration In X Maculatusmentioning
confidence: 99%
“…34,42,43 The distribution of the pigments in pterinophores, as Valenti and Kallman 34 termed them, was lutein at the center and pterinosomes containing drosopterin at the periphery. They concluded that the red coloration stems from the pterin, drosopterin.…”
Section: Red Orange and Yellow Body And Dorsal Fin Colorationmentioning
confidence: 99%
See 2 more Smart Citations